Synthesis of High-Brightness Blue-Emitting Phosphors Sr2MgSi2O7:Eu2+, Er3+ by Gel-Combustion Method Assisted by Microwave and their Properties - Zhai, Yong-Qing; Chen, Juan; Wang, Li-Li; Ma, Jian; Hu, Zhi-Chun (Asian Journal of Chemistry, 2013)
High-brightness blue emitting phosphors Sr2MgSi2O7:Eu2+, Er3+ were synthesized successfully by gel-combustion method assisted by microwave. The as-synthesized phosphors were analyzed and characterized by X-ray diffraction and fluorescence spectrophotometer. The influences of co-doped Er3+ concentration, fuel urea and flux H3BO3 on luminescent properties of samples were investigated. The results show that Sr2MgSi2O7: Eu2+, Er3+ phosphors possess the tetragonal crystal structure similar to that of Sr2MgSi2O7. The excitation spectrum shows a broad band from 250 to 450 nm and the strongest excitation peak is at 358 nm. The emission spectrum excited by 358 nm also shows a wide band with the main peak at ca. 467 nm, which is ascribed to the typical transition from 4f65d1 to 4f7 of Eu2+. It is found that co-doped Er3+ can sensitize effectively the luminescence of Eu2+ ions in Sr2MgSi2O7 host. The luminescence intensity reaches the strongest when the concentration of co-doped Er3+ is 0.01, the mass ratio of urea to nitrate is 1.5:1 and the mole fraction of H3BO3 is 15 % and it is about 1.3 times of single-doped Eu2+ sample.